ANALYSIS OF TECHNICAL RISK AT CONSTRUCTION PROJECT BY USING FUZZY LOGIC METHOD (CASE STUD: GRAND SUNGKONO LAGOON) - Dwi Praseptiawan Rhosani; Yeny Dhokhikah; Anita Trisiana (Universitas Jember, 2020)
The High Rise Building Construction projects have a complexity of the work and a complex structural design that cause the large possibility of technical risk. It is crucial to do a technical risk assessment analysis for the classification of technical risk and how to handle it. The purpose of this research was to identify technical risks and risk responses to high category technical risk in the Grand Sungkono Lagoon project, Surabaya. The identifications were done by conducting a validated literature study with a preliminary survey. This research used a fuzzy logic method to assess the process of technical risk and it was assisted with MATLAB 2015a application by distributing the main questionnaire to selected respondents. From the result of the analysis, there were 7 high-level technical risk variables which consist of the effect of weather on the implementation, the difficulty mounting formwork and scaffolding at altitude, the existence of design changes, re-work, unsuitable system planning, poor equipment maintenance and wrong implementation methods. Proyek konstruksi High Rise Building memiliki kompleksitas pekerjaan dan desain struktur yang rumit sehingga kemungkinan terjadinya risiko teknis sangat besar. Analisis penilaian risiko teknis sangat penting dilakukan untuk penggolongan risiko teknis dan cara penanganannya. Tujuan penelitian ini adalah untuk mengidentifikasi risiko teknis dan respon risiko terhadap risiko teknis kategori tinggi pada proyek Grand Sungkono Lagoon, Surabaya. Identifikasi dilakukan dengan melakukan studi literatur yang divalidasi dengan survey pendahuluan. Proses penilaian risiko teknis pada penelitian ini menggunakan metode Fuzzy Logic dibantu aplikasi MATLAB 2015a dengan menyebarkan kuisioner utama pada responden terpilih. Hasil analisis di dapat 7 variabel risiko teknis kategori tinggi yaitu pengaruh cuaca pada pelaksanaan, kesulitan pemasangan bekisting dan perancah di ketinggian, adanya perubahan desain, pekerjaan ulang, system yang tidak sesuai perencanaan, pemeliharaan peralatan yang buruk dan metode pelaksanaan yang salah.